Is Carrying Feathers a Sexually Selected Trait in House Sparrows?. (13th January 2013) - García‐López de Hierro, Lola; Moleón, Marcos; Ryan, Peter G.
Abstract: Males in several avian groups carry specialised materials as part of their courtship display. Females may vary their investment in reproduction in relation to their mates' attractiveness. The house sparrow ( Passer domesticus ) population on Dassen Island, South Africa, builds domed nests in the branches of trees. These nests are more or less spherical structures with a deep cup lined largely with feathers. When males collect feathers, they call to females and display the feather before it is added to the nest. We examined whether carrying feathers provides females with an index of male quality, which correlates with their subsequent investment in parental care. Additionally, we studied the potential importance of feathers in nest insulation. Feathers were collected mainly by males. Males also brought larger feathers, and deposited more feathers in nests, than females. Number of trips with feathers – which increased after feathers were experimentally removed from nests – and number of feathers brought varied among males. Volume of feathers influenced females' investment in reproduction and positively correlated with clutch size and chick feeding rates. We found more feathers during incubation and immediately after chicks hatched, when nest heat requirements peak. Furthermore, number of trips with feathers and number and size of feathers were greater during incubation. Our results suggest that this feather‐carrying behaviour by male house sparrows influences maternal reproduction investment and could be a kind of parental care per se by supplementing nest insulation.